Pre-purchase information search: too many sources to choose. Issue 3 (8th August 2016) - Broilo, Patricia Liebesny; Espartel, Lélis Balestrin; Basso, Kenny
Abstract : Purpose: Due to the increasing volume of information spread in physical and online environments, a consumer intending to purchase a product or service must choose not only what to buy but also which sources to consult when searching for information that may aid decision making. This study aims to understand how consumers choose their sources of information in pre-purchase external searches, given the information overproduction scenario. Design/methodology/approach: Using a qualitative approach, data collected through interviews with consumers were analyzed under the technique of content analysis, and the results were synthesized into a framework. Findings: Consumers tend to consider few sources of information, based on a previously built perception of which sources are more or less appropriate for consultation. Choice tends to be based on pre-established evaluation criteria involving the use of heuristics in the form of socialized images regarding those sources. Research limitations/implications: Despite the study's exploratory nature, the proposed framework sheds light into how consumers respond to information overproduction when choosing their sources, providing interesting venues for future investigations. Practical implications: The study identified the possible occurrence of consumer confusion associated with information sources, extending the theoretical understanding of such a concept. Moreover, it revealed the need for managers to consider specific aspects related to the sources to be included in marketing communications. Originality/value: This is the first study to address choice of information sources associated with consumer confusion focusing the offline/online scenario.